Breen, Ed., The Power The Words - Documents In American History - Barnes, Howard (Teaching History: A Journal of Methods, 1997)
These volumes of readings in United States history to and from 1865 are welcome additions to the genre. T. H. Breen has chosen a large number of short primary sources. There are 117 and 123 documents in the first and second volumes respectively, for an average of7 or 8 per chapter. Each document has a one-paragraph introduction and each of the 15 chapters in Volume 1 and the 16 chapters in Volume 2 has a longer introduction. The chronological organization is conventional. The last chapter of Volume 1 on Reconstruction becomes the first chapter of Volume 2.